A comparison of taxonomy and ontology for classifying knowledge resources in an organization. - Chan, Danny Hong Kee. (2008)
This study compares the applicability and effectiveness of taxonomy and ontology information classification to help the Ministry of Home Affairs to achieve a higher level of information integrity and accuracy in information storage, retrieval, sharing and reuse. As there was little study comparing the effectiveness of taxonomy and ontology classification methods, the study compares the taxonomy and ontology building process using terrorism related information available from the public domain. A prototype taxonomy and ontology were then developed for user testing and feedbacks.